PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI DI INDONESIA PERIODE 2018-2021 - Novitasari, Budi Tiara (STAI Darul Qalam Tangerang, 2023)
Indonesia is the fourth most populous country in the world with considerable fossil energy consumption. This study attempts to explore the corporate social responsibility disclosures of energy sector companies operating in Indonesia. This study uses descriptive analysis and trend analysis approaches. The analysis is conducted by comparing the proportion of disclosures that have been made with the disclosures that should be made based on the Global Reporting Initiatives (GRI). The results of the analysis show that energy sector companies in Indonesia still have fairly low disclosures (less than 50%) in the 2018-2021 period. However. There is a positive trend in social responsibility disclosure during the same period